Development of the Viable System Model of Partner Relationship Management of the Company - Fedotova, Iryna; Shynkarenko, Volodymyr; Kryvoruchko, Oksana (International Journal of Engineering and Technology, 2018)
This paper considers the main instruments for relationship management between the company and different partners. The purpose of the study is to improve the theoretical foundations of the development of a system of total relationship management of the company with the main groups of interaction actors, taking into account relationships with all groups of partners of the company. The model of the relationship management system of the company on the basis of methodical apparatus of cybernetic modeling of viable systems is proposed. The model of the relationship management system of the company is presented as an entity (a metasystem) and an object of management (operating element), which is proposed in the form of relationship management processes with main groups of partners. The system of inter-company interactions, which reflects the development of individual relationship with a certain partner, is presented. Based on the structural-level and metasystem approaches, key levels and structure of enterprise relationships are identified. Five levels of relationship between the company and its partners â€“ element, component, subsystem, system-wide, and metasystem levels are identified. These levels are presented in the form of recursive structure of the viable model of relationship management system of the enterprise. Â Â